HibisTrade application - Yusra, Nur Fatihah; Japre, Fatin Nurdiana; Mohd Hazrinuddin, Muhammad Wafi; Ahmad Syahir, Ariff Danial; Hashim, Nurhaslinda (Universiti Teknologi MARA, Negeri Sembilan, 2025)
HibisTrade is an innovative digital application designed to address challenges in navigating complex regulations, managing logistics, and ensuring compliance in the international trade environment. The application helps users, especially businesses, stay compliant with evolving international regulations, including tariff classification, documentation standards, and sustainability requirements under the ESG framework. HibisTrade enables its users to better understand and control logistics management to avoid overstocking or stockouts. Additionally, the application offers practical support to help SMEs enter international markets.